Advanced treatment of direct dye wastewater using novel composites produced from hoshanar and sunny grey waste - Akhtar, Amna; Hanif, Muhammad Asif; Rashid, Umer; Bhatti, Ijaz Ahmad; Alharthi, Fahad A.; Kazerooni, Elham Ahmed (MDPI AG, 2022)
The present project is designed to investigate the potential of hoshanar and sunny grey marble wastes to remove direct violet 51 dye from wastewater using adsorption process. The effect of different parameters such as pH, adsorbent dose, initial dye concentration, and contact time were studied to optimize the results of adsorption process. Different isothermic models (Temkin, Langmuir isotherm, Freundlich isotherm, Harkin Jura, and Dubinin-Radushkevich models) and kinetic models (pseudo-first order and pseudo-second order) were employed to adsorption data to find out the best fit model, i.e., Langmuir isotherm and pseudo-second order model. Marble waste composites were also characterized by using different techniques such as scanning electron microscopy (SEM) for surface morphology and Fourier transform infrared spectroscopy (FTIR) to determine chemical arrangements, structure, and functional groups of adsorbents. Hoshanar treated with a mixture of potassium ferricyanide, and sodium meta silicate showed maximum adsorption capacity of 105.31 mg/g as compared to untreated hoshanar (67.19.45 mg/g). So, the conversion of HM into HMPS makes it an affordable, efficient, and available adsorbent for wastewater treatment.